URGENSI KESEHATAN JASMANI DALAM PENDIDIKAN ISLAM - Saputra, Dedi; AR, Muhammad; Hidayat, Rahmad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Islam gives important attention to every part of human life, physical health is an important part of Islamic education so it must be given equal attention to education in faith, morals and reason. Recently, the study of physical health from an Islamic perspective has rarely been touched upon. This study discusses the urgency of physical health from an Islamic education perspective. This research uses the Library Research method on several pieces of literature such as the Al-Qur'an, hadith, books, books and several related articles. From several literatures it has been found that the only way to achieve quality 'ubudiyah is by having a healthy and strong body. To achieve this, all physical matters need serious attention. In Islam there are at least three stages of physical maintenance as per the message of the Al-Qur'an and the hadith of the Prophet Muhammad, firstly maintaining personal and environmental cleanliness, secondly consuming halal and healthy food and drinks and thirdly doing physical activity and sports. These three things are urgent for every human body to give the body the right to be able to worship, work and carry out other routines.